Technology and the New Professionalization of Teaching. Issue 12 (December 2015) - Shaffer, David Williamson; Nash, Padraig; Ruis, A. R.
Background: By 2009, 99% of U.S. classrooms had access to computers, with an average ratio of 1.7 students per computer, and 40% of teachers report using computers often in their classrooms. However, while K–12 schools are investing more heavily in digital technologies, only a small fraction of this investment is going to instructional software (7%) and digital content (5%). Education policy leaders have called for increased investment in and use of digital learning technologies in K–12 education, which has significant professional implications for the 40% of teachers who use computers often and, perhaps more importantly, for the 60% who do not. Objective: This article explores for a broad audience the changing landscape of education in the digital age, the changing roles of teachers in a technology-rich education system, and the skills, knowledge, values, and ways of thinking that teachers will need to have to support students' social, emotional, and intellectual development in a digital learning environment. Research Design: This analytic essay reviews and synthesizes research on learning in a digital environment, providing theoretical framework for understanding the changing landscape of learning in technology-rich environments and the consequent changes in teacher preparation that this may entail. Conclusion: We explore the influence of educational technologies on teaching and teacher preparation by looking at three kinds of learning technology: digital workbooks that help students learn basic skills through routine practice; digital texts, such as ebooks, virtual museums, and learning games, that provide students with mediated experiences; and digital internships that simulate real-world practices, helping students learn how to solve problems in the ways that workers, scholars, and artists in the real world do. We examine the extent to which these technologies can assume different aspects of teachers' traditional functions of assessment, tutoring, and explication. We argue that increased use of these and other digital learning technologies could allow teachers to provide more nuanced curricula based on their students' individual needs. In particular, teachers will likely assume a new role, that of a coordinator who provides guidance through and facilitation of the learning process in individual students' social, intellectual, and emotional contexts. We suggest this may require changes to teacher preparation and in-service professional development to help both new and experienced teachers succeed in an ever-changing digital learning environment, as well as new methods of evaluating teacher performance that account for more than student achievement on standardized tests. Interesting things happen along borders—transitions—not in the middle where everything is the same. —Neal Stephenson, Snow Crash